Pembentukan Pendidikan Karakter Peduli Lingkungan Siswa di MTsN 16 Jombang - Noviana, Risma Yoga; Kholid, Abd; Fodhil, Muhammad (Universitas KH. A. Wahab Hasbullah, 2022)
MTsN 16 Jombang is a madrasah located on the outskirts of Jombang district. Several years ago it had limitations. With limitations, the madrasah wanted to make madrasahs with environmental characteristics. One of them is being able to implement a madrasah that has the character of caring for the environment, until now this madrasah has occupied the national level Adiwiyata madrasah. Character education is an effort to shape the human personality for the better based on existing values. environmental care, namely attitudes and actions that always try to prevent damage to the natural environment around them. This research uses a qualitative approach. While data collection uses: interviews and observation and documentation. The results of the study were students' concern for the environment, namely that most of the students there really cared about their environment. The strategy for the formation of character education is socialization every day, the formation of working groups, awareness raising, mutual commitment, and discipline. The obstacles are environmental problems, the character of each child is not the same, few students still throw garbage outside the trash can. To support it, always remind both teachers, students, facilities and facilities, the environment that supports, for example, from the surrounding community.